2021
DOI: 10.3389/fpubh.2021.661482
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic Uncertainty and Socially Responsible Investments

Abstract: This paper examines the effects of pandemic uncertainty on socially responsible investments. We use the overall corporate sustainability performance index in the Global-100 Most Sustainable Corporations in the World dataset to measure socially responsible investments. The global pandemic uncertainty is also measured by the World Pandemic Uncertainty Index. We focus on the panel dataset from 2012 to 2020, and the results show that the World Pandemic Uncertainty Index is positively related to socially responsibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…(Taobao and Tmall, 3-10) New online business models developed to 108 "Ctrip announces the launch of activities of 'scenic spot cloud tourism', combining with eight suppliers to open nearly 7,000 voice tour products of more than 3,000 scenic spots for free." (Ctrip,(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) transform original offline transactions "We will provide free tourism promotion services to all tourism destinations joining the 'Ark alliance', mainly in the form of VR and HD video materials suitable for consumers to browse online." (Tongcheng-Elong, 2-11) "We develop a function of 'live broadcast' to purchase second-hand cars.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Taobao and Tmall, 3-10) New online business models developed to 108 "Ctrip announces the launch of activities of 'scenic spot cloud tourism', combining with eight suppliers to open nearly 7,000 voice tour products of more than 3,000 scenic spots for free." (Ctrip,(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) transform original offline transactions "We will provide free tourism promotion services to all tourism destinations joining the 'Ark alliance', mainly in the form of VR and HD video materials suitable for consumers to browse online." (Tongcheng-Elong, 2-11) "We develop a function of 'live broadcast' to purchase second-hand cars.…”
Section: Discussionmentioning
confidence: 99%
“…at the macro-level intended to elucidate the factors influencing general CSR actions 13,14 . In addition, there were studies on the micro-level CSR practices in different companies and industries, such as hotels 15 , the media 16 , telecoms corporations 17 , the United States CSR leaders 18 , private sector in Iran 19 .…”
Section: Introductionmentioning
confidence: 99%
“…These uncertainties usually damage domestic and global economies (Salisu and Akanni 2020). In previous work, researchers indicated that uncertainty was one of the important factors influencing investment decisions (Vickman et al 2012;Zhu et al 2021). Therefore, uncertainty needs to be incorporated in the decision making process.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several recent studies have investigated the impact of uncertainty concerning stock market returns and volatilities (Coskun et al 2020). Bakas and Triantafyllou (2020), Chiah and Zhong (2020), Albulescu (2021), Hemrit andBenlagha (2021), andZhu et al (2021) studied the link between the World Pandemic Uncertainty Index (WPUI) and different stock market indices and found a negative link. On the other hand, Wang et al (2021) examined the association between uncertainty and S&P 500 returns and found that the uncertainty related to the COVID-19 pandemic was positively linked to the stock return index.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Numerous countries have enacted various sorts of lockdowns and quarantines, adding to the tension and panic. Due to a lack of medical supplies, particularly masks and respirators, international rivalry for masks and respirators has pushed hospitals and health centers to restrict their supplies [12]. These reasons have contributed to an increase in global insecurity.…”
Section: "Black Shawn Events" Uncertainty and Risk Managementmentioning
confidence: 99%